The Association of HLA-G Gene Polymorphism and Its Soluble Form With Male Infertility - Piekarska, Karolina; Radwan, Paweł; Tarnowska, Agnieszka; Wiśniewski, Andrzej; Krasiński, Rafał; Radwan, Michał; Wilczyński, Jacek R.; Malinowski, Andrzej; Nowak, Izabela (Frontiers in Immunology, 2022)
Successful reproduction depends on many factors. Male factors contribute to infertility in approximately 50% of couples who fail to conceive. Seminal plasma consists of secretions from different accessory glands containing a mixture of various cytokines, chemokines, and growth factors, which together can induce a local immune response that might impact on a male’s as well as a female’s fertility. Human leukocyte antigen (HLA)-G expression has been suggested as an immunomodulatory molecule that influences pregnancy outcome. The HLA-G gene encodes either membrane-bound or/and soluble proteins. The aim of this study was the evaluation of HLA-G polymorphisms and their impact on soluble HLA-G (sHLA-G) production. We tested the HLA-G polymorphism in three positions: rs1632947: c.-964G>A; rs1233334: c.-725G>C/T in the promoter region; rs371194629: c.∗65_∗66insATTTGTTCATGCCT in the 3′ untranslated region. We tested two cohorts of men: 663 who participated in in vitro fertilization (test material was blood or sperm), and 320 fertile controls who possessed children born after natural conception (test material was blood). Since 50% of men visiting assisted reproductive clinics have abnormal semen parameters, we wondered if men with normal sperm parameters differ from those with abnormal parameters in terms of HLA-G polymorphism and secretion of sHLA-G into semen. We found that certain rs1632947-rs1233334-rs371194629 HLA-G haplotypes and diplotypes were associated with male infertility, while others were protective. Normozoospermic men with the A-C-del haplotype and A-C-del/A-C-del diplotype secreted the most sHLA-G into semen (574.1 IU/mL and 1047.0 IU/mL, respectively), while those with the G-C-ins haplotype and G-C-ins/G-C-ins diplotype – the least (80.8 IU/mL and 75.7 IU/mL, respectively). Men with the remaining haplotypes/diplotypes secreted sHLA-G at an intermediate level. However, only in one haplotype, namely G-C-ins, did we observe strong significant differences in the concentration of sHLA-G in the semen of men with teratozoospermia compared to men with normal sperm parameters (p = 0.009). In conclusion, fertile men differ in the profile of HLA-G polymorphism from men participating in IVF. Among all HLA-G haplotypes, the most unfavorable for male fertility is the G-C-ins haplotype, which determines the secretion of the lowest concentration of the soluble HLA-G molecule. This haplotype may reduce sperm parameters.